Alpha-chain Disease with Clinical, Immunological, and Histological Recovery. Issue 5916 (25th May 1974) - Manousos, O. N.; Economidou, J. C.; Georgiadou, D. E.; Pratsika-Ougourloglou, K. G.; Hadziyannis, S. J.; Merikas, G. E.; Henry, K.; Doe, W. F.
Abstract : Clinical, immunological, and histological recovery in a patient with alpha-chain disease is described. The patient, a 27-year-old Greek man, presented with severe steatorrhoea, abdominal pain, oedema, and hypogammaglobulinaemia. Treatment with tetracycline produced only temporary remission. Intermittent therapy with prednisone and cyclophosphamide together with antibiotics was followed by clinical recovery, return of histological appearances of the small intestine to normal, and disappearance of free alpha-chain protein from the serum. The patient remained well one year later without treatment.